Future Anxiety Among Young People Affected by War and Armed Conflict: Indicators for Social Work Practice - Alotaibi, Nouf M. (Frontiers in Sociology, 2021)
Strengthening the evidence base for professional social work intervention that contributes to providing psychosocial support to international students affected by war and conflict is a major priority as this vulnerable group of youth increases. Therefore, this study aimed to determine the level of future anxiety among international students coming from areas experiencing war and conflict. This study was conducted on 287 young people affected by wars and conflicts. Findings showed a statistically significant relationship between the demographic variables and the level of future anxiety. Also, there is a statistically significant relationship between future anxiety and some variables related to war and conflict. The study recommends developing psychosocial support services for this vulnerable group, considering the cultural context to promote women and protect them from discrimination in the services they deserve on an equal basis with men.